Effects of Salinity Stress on Physiological Responses and Growth Impacts of Horticultural Crops: A Literature Review - Cahya Rudiana Putri (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
Salinity stress is a major constraint in horticultural crop production, affecting plant growth, yield, and quality. Excessive salt accumulation in soil and irrigation water induces osmotic stress and ion toxicity, which disrupt physiological processes in plants. This literature review aims to analyze physiological responses and growth impacts of various horticultural crops under salinity stress. The reviewed studies include ten horticultural commodities: tomato, cayenne pepper, mungbean, leaf mustard, cucumber, red spinach, shallot, sambiloto, ginger, and moth orchid. The synthesis indicates that plant responses to salinity vary considerably among species and varieties. Mungbean is highly sensitive, showing growth and yield reductions at relatively low salinity levels. In contrast, cayenne pepper var. Dewata and red spinach are able to maintain growth under higher salinity conditions. Salinity effects are generally more pronounced during the reproductive stage, as reflected by reductions in yield components such as seed weight and fruit diameter, along with physiological disturbances including decreased chlorophyll content and increased oxidative stress. In medicinal plants such as sambiloto, mild salinity stress may enhance the accumulation of bioactive compounds despite suppressing vegetative growth. These findings highlight the importance of commodity-specific salinity management strategies that consider both physiological tolerance and cultivation objectives in horticultural production systems.